Making sense of ecopreneurs' decisions to sell up - Kearins, KN; Collins, E (John Wiley & Sons, Ltd and ERP Environment, 2011)
This article examines the phenomenon of values-based firms being sold to larger mainstream firms. Its focus is on the sensemaking rationale offered by a New Zealand ecopreneur who sold an organic beverage company after 20 years at the helm. The company case study is presented through two enterprise development narratives based on alternative sensemaking modes. Key values-related challenges arising in ecopreneurial business are identified, including (1) adhering to the founder's values, (2) growing the business sustainably, (3) deciding whether and when to expand ownership to cope with undercapitalization, (4) deciding who to bring in as new owners to ensure values alignment, (5) determining how and when the founder might leave and (6) ensuring the attractiveness of the sustainability values so that they might be retained. Other factors implicated in the sale of values-based firms are also postulated. It is argued that, although ecopreneurs might be accused of selling out their principles by selling up, there is some evidence that eco-brands are being maintained and that growth prospects could be improved after acquisition. Serial ecopreneurship may even extend social benefits.
Keywords: Ecopreneurship; Enterprise development; Sensemaking